1988
DOI: 10.4141/cjss88-001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crop Rotation and Fertilization on the Quantitative Relationship Between Spring Wheat Yield and Moisture Use in Southwestern Saskatchewan

Abstract: this has resulted in substantially greater moisture use efficiency in recent years likely due to better, more timely crop management and the improved cereal varieties now used. When y was related to AvSpSM and GSP ( I May to 31 July) analyzed as separate variables, the relationship was only improved in terms of coefficient of determination (R2) value when a quadratic model was used. However, the latter did not predict the 1985 and 1986 yields as well as the y vs. MU relationship did. For fallow-seeded wheat, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 5 publications
(6 reference statements)
6
56
1
Order By: Relevance
“…These results appear to agree with those of Campbell et al (1988); they found that the period from shot-blade to soft-dough stage was the most important time for precipitation in an 18-yr (1967-1984) field study of spring wheat grown on fallow at Swift Current. The important period for MaxDT also peaks near the first week of July, but extends into early August.…”
Section: Moving-mean Analysissupporting
confidence: 81%
“…These results appear to agree with those of Campbell et al (1988); they found that the period from shot-blade to soft-dough stage was the most important time for precipitation in an 18-yr (1967-1984) field study of spring wheat grown on fallow at Swift Current. The important period for MaxDT also peaks near the first week of July, but extends into early August.…”
Section: Moving-mean Analysissupporting
confidence: 81%
“…Thus, in all years conditions were adequate for plant emergence and growth of wheat and above average for grain production. Precipitation during the months of May, June and July are particularily important to yield in the semiarid prairies (Campbell et al 1988) and in all years precipitation in these months were average to above average.…”
Section: Weathermentioning
confidence: 99%
“…2c), but performed less well in estimating yields for F-W-(W) (r 2 = 0.38 * , RMSE = 366) or Cont W (r 2 = 0.42 * , RMSE = 335) each receiving P but no N (data not shown). Thus, our model will perform best in cases where nutrient inputs are balanced with respect to both N and P. We did not include data for 1970 in our prediction of the rotation data because, although this was a year with above average GSP, 70% of the GSP came between June 10-18th (Campbell et al 1988). Most of this precipitation was likely lost via leaching.…”
Section: Model Validationmentioning
confidence: 99%
“…This ongoing study, which was conducted at SPARC, is described elsewhere (Campbell et al 1983;Campbell et al 1988); thus, only a brief description is presented. The study, which involves 12 wheat-based rotations initiated in 1967, uses conventional tillage management and compares crop types, fertilizer treatments, and cropping intensities.…”
Section: Experiments 3 Long-term Crop Rotation Study At Swift Currentmentioning
confidence: 99%
See 1 more Smart Citation